Indefinite Ruhe’s Variant of the Block Lanczos Method for Solving the Systems of Linear Equations - M. Ghasemi Kamalvand; K. Niazi Asil (Advances in Mathematical Physics)
In this paper, we equip Cn with an indefinite scalar product with a specific Hermitian matrix, and our aim is to develop some block Krylov methods to indefinite mode. In fact, by considering the block Arnoldi, block FOM, and block Lanczos methods, we design the indefinite structures of these block Krylov methods; along with some obtained results, we offer the application of this methods in solving linear systems, and as the testifiers, we design numerical examples.